(untitled) (Al-Academy, 2026)
This research is a new reading of antithetical binaries in general, and in the artistic field in particular, so the concept was delved into and explored in the roots - that is, the first signs, because antithetical binaries in the artistic field remain in need of conceptual foundations, especially since there is a noticeable scarcity in this field, and I can even say that they are almost non-existent, which gave me an impression and an incentive to delve, explore and investigate so that I may contribute to helping those interested in the artistic field in tracking, tracing and monitoring this concept. Therefore, the research included four chapters, the first chapter was devoted to stating the research problem, which resulted in the following questions: How did the Turkish artist employ antithetical binaries in his visual texts? What are antithetical binaries? What are their mechanisms and principles? And did digital technology play a role in enriching the contemporary artist? The second chapter included two topics. The first topic dealt with the antithetical dualities between concept and meaning. The second topic included digital art, a historical reading. The third chapter included the research procedures, in which the framework of the research community was determined, and the sample models, totaling (4) four artistic models,were selected for the artist Ugur Galenkus.The treatments for managing the research and analyzing the sample models were reviewed, while the fourth chapter dealt with the research results, their discussion and conclusions.